2022
DOI: 10.3390/ani12213007
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Oregano Essential Oil Supplementation Influences Production Performance and Gut Microbiota in Late-Phase Laying Hens Fed Wheat-Based Diets

Abstract: This study aimed to investigate the potential effects of OEO on production performance, egg quality, fatty acid composition in yolk, and cecum microbiota of hens in the late phase of production. A total of 350 58-week-old Jing Tint Six laying hens were randomly divided into five groups: (1) fed a basal diet (control); (2) fed a basal diet + 5 mg/kg flavomycin (AGP); (3) fed a basal diet + 100 mg/kg oregano essential oil + 20 mg/kg cinnamaldehyde (EO1); (4) fed a basal diet + 200 mg/kg oregano essential oil + 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 59 publications
1
14
2
Order By: Relevance
“…showed that the addition of GML (1000 mg kg −1 ) significantly improved the average egg weight and laying rate of Lohmann Grey layers aged 66 weeks and reduced the FCR and defective egg rate. There was evidence that dietary supplementation with 200 mg kg −1 oregano essential oil and 20 mg kg −1 cinnamaldehyde improved laying performance, decreased FCR, and altered the fatty acid and microbial composition of eggs from 58‐week‐old Jing Tint 6 laying hens 20 . However, in the current study, the effect of GCM on the production performance of layers at the early laying stage was only reflected in the reduced rate of unqualified eggs.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…showed that the addition of GML (1000 mg kg −1 ) significantly improved the average egg weight and laying rate of Lohmann Grey layers aged 66 weeks and reduced the FCR and defective egg rate. There was evidence that dietary supplementation with 200 mg kg −1 oregano essential oil and 20 mg kg −1 cinnamaldehyde improved laying performance, decreased FCR, and altered the fatty acid and microbial composition of eggs from 58‐week‐old Jing Tint 6 laying hens 20 . However, in the current study, the effect of GCM on the production performance of layers at the early laying stage was only reflected in the reduced rate of unqualified eggs.…”
Section: Discussioncontrasting
confidence: 68%
“…There was evidence that dietary supplementation with 200 mg kg −1 oregano essential oil and 20 mg kg −1 cinnamaldehyde improved laying performance, decreased FCR, and altered the fatty acid and microbial composition of eggs from 58-week-old Jing Tint 6 laying hens. 20 However, in the current study, the effect of GCM on the production performance of layers at the early laying stage was only reflected in the reduced rate of unqualified eggs. The reason for the difference in the experimental results may be the difference in the breed and weekly age of laying hens and the amount of GML and cinnamaldehyde added.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Cinnamaldehyde is one of the active components in Cinnamomum cassia , which has a series of pharmacological effects such as antifungal, antibacterial and anti-tumor ( Kaur et al, 2019 ). Dietary supplementation with oregano essential oil (200 mg/kg) and cinnamaldehyde (20 mg/kg) could improve production performance and reduce feed conversion efficiency of laying hens in later period by selectively regulating cecal microbial community ( Gao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%